The Value of Contrast-Enhanced Ultrasound in the Diagnosis of Cesarean Scar Pregnancy. - Xiong, Xi; Yan, Ping; Gao, Chunyan; Sun, Qiulei; Xu, Fenglian (BioMed Research International, 2016)
Objective. To evaluate the value of contrast-enhanced ultrasound (CEUS) in the cesarean scar pregnancy (CSP). Methods. Clinical data from 92 patients with lower uterine segment pregnancy, who underwent conventional ultrasound and CEUS examination in the Department of Obstetrics and Gynecology, were collected by Xinqiao Hospital Third Military Medical University from March 2014 to March 2015. The parameters of ultrasound contrast time-intensity curve (TIC), including arrival time, time to peak, time from peak to one half, basic intensity, peak intensity, and wash-in slope, were analyzed. Results. Of the 92 cases of patients with pregnancy in the lower uterine segment, 52 cases were CSP, and 40 cases were intrauterine pregnancy. CEUS was significantly better than conventional ultrasound in terms of sensitivity, negative predictive value, Youden index, and diagnostic accuracy (P<0.05). There was no significant difference in specificity and positive predictive value (P>0.05). Conclusion. CEUS has a higher accuracy than conventional ultrasound in diagnosis of CSP.